Strengthening students' social awareness based on religious extracurriculars (Rohis) at one of the high schools in Jakarta, Indonesia - Rokib, Rokib; Zaimudin, Zaimudin; Ghofur, Abdul (Universitas Wiralodra, 2023)
This research aims to analyze the implementation of religious extracurriculars (Rohis) in strengthening students' social awareness and analyzing strategies and supporting and inhibiting factors in enhancing students' social understanding in religious extracurriculars (Rohis) at SMAN 74 Jakarta. The research method used is a descriptive case study approach. Analysis with a focus on field research. Research data was collected through observation, interviews, and document analysis, which was then analyzed using a flow model with analysis procedures consisting of data reduction, data presentation, and conclusion. The research results show that implementing religious extracurriculars (Rohis) at one of the high schools in Jakarta, Indonesia has succeeded in creating an environment that promotes cooperation, empathy, and respect for others. Through social service activities, students become more sensitive to social problems around them and show higher social awareness. The strategies Rohis coaches and members carried out to strengthen students' social understanding include implementing teaching and integrating social awareness values ​​in regular meetings, providing good role models, and involving students in social activities in the school and community environment. Overall, this research provides important insights into the role of Rohis in forming students' social awareness and offers recommendations to further increase the effectiveness of religious extracurriculars in fostering social understanding among students at one of the high schools in Jakarta, Indonesia.